Intensified photocatalytic degradation of methylene blue over Fe supported on dendritic fibrous SBA-15: Optimisation, kinetic, isotherm, and reusability - R. S. R., Mohd Zaki; A. A., Jalil; Herma Dina, Setiabudi (Elsevier Ltd, 2023)
A novel photocatalyst, Fe supported on dendritic fibrous SBA-15 (Fe/DFSBA-15), is synthesised and employed for methylene blue (MB) photocatalytic degradation. The DFSBA-15 was synthesised by applying a microemulsion technique and SBA-15 crystal-seed crystallisation approach. The TEM and FESEM of Fe/DFSBA-15 revealed the revolution of rod-typed SBA-15 into dendritic fibrous-structured (DFSBA-15). The characterisation analyses using FTIR, XRD, BET, PL and UV-Vis DRS, confirmed favourable properties of Fe/DFSBA-15 compared to Fe/SBA-15. Fe/DFSBA-15 exhibits superior properties, attributed to its unique dendritic fibrous morphology that increases the surface area, pore accessibility, and mass transfer. These exceptional features establish it as a highly promising and efficient photocatalyst for diverse applications. Optimisation of MB degradation (Y, %) by using Fe/DFSBA-15 was conducted by employing response surface methodology (RSM) of independent parameters such as catalyst loading (X1, 0.5 – 2.0 g/l), pH (X2, 6 – 10) and initial MB concentration (X3, 10 – 50 mg/l). The model was significant, and MB degradation was optimised at 99.54% (X1 = 1.66 g/l, X2 = 9, and X3 = 27.5 mg/l) along with validation experiments (3.62% error). The research outcome was in agreement with the Langmuir second-order (R2 ≥ 0.99), indicating a predictable trend of the MB degradation process. Interestingly, the excellent degradation and reusability performance of Fe/DFSBA-15 offered a prospective approach for industrial wastewater treatment.